Weekly vs. Every-3-Week Paclitaxel and Carboplatin for Ovarian Cancer - Chan, John K; Brady, Mark F; Penson, Richard T; Huang, Helen; Birrer, Michael J; Walker, Joan L; DiSilvestro, Paul A; Rubin, Stephen C; Martin, Lainie P; Davidson, Susan A; Huh, Warner K; O’Malley, David M; et al. (The New England journal of medicine, 2016)
The dose-dense delivery of chemotherapy (greater frequency of drug delivery) was explored in women with advanced ovarian cancer. All patients received carboplatin; half received paclitaxel weekly and half every 3 weeks. There were no between-group differences in progression-free survival. Ovarian cancer, the most lethal gynecologic cancer, is responsible for approximately 14,000 deaths in the United States annually. 1 The incorporation of bevacizumab, a monoclonal antibody against vascular endothelial growth factor, in the treatment regimen prolongs progression-free survival but not overall survival. 2 – 5 A dose-dense regimen of paclitaxel involving greater frequency of drug delivery may enhance its antineoplastic effect by eliciting antiangiogenic and proapoptotic properties. 6 – 9 Weekly paclitaxel therapy prolonged survival among patients with early-stage breast cancer and those with metastatic breast cancer. 10 , 11 In a study involving patients with ovarian cancer, Japanese investigators found that dose-dense weekly paclitaxel prolonged progression-free . . .